Giant cell interstitial pneumonia secondary to cobalt exposure from e-cigarette use. Issue 6 (5th December 2019) - Fels Elliott, Daffolyn Rachael; Shah, Rupal; Hess, Catherine Ann; Elicker, Brett; Henry, Travis S.; Rule, Ana Maria; Chen, Rui; Golozar, Mehdi; Jones, Kirk D.
The spectrum of pulmonary disease caused by e-cigarette use is currently emerging and appears to be multifaceted [1]. We describe a patient who developed pathologically documented giant cell interstitial pneumonia following regular use of an e-cigarette. This disorder has been termed hard metal pneumoconiosis, or cobalt lung, due to its close association with exposure to hard metal (cemented tungsten carbide with cobalt) [2]. Analysis of the device's e-liquid revealed significant levels of cobalt, supporting a diagnosis of giant cell interstitial pneumonia associated with inhaled cobalt from regular e-cigarette use. An e-cigarette user developed giant cell interstitial pneumonia, a rare disease largely limited to work exposure to hard metals, including cobalt. Analysis of the e-liquid identified significant levels of cobalt, supporting the e-cigarette's causative role. http://bit.ly/2VRcT1U